An in vitro study on the sealing ability ofnano hydryapatite and standard hydroxyapatite on dentinal tubules - Masudi, Sam'an Malik; Samsudin, Ab. Rani; Salihi, Karima Akool Al; Omar, Nor Shamsuria (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2004)
Dentin hypersensitivity is a con1mon clinical problem; with incidence of 15% to 30o/o of the population at the age between 20 and 40 years. Previous study revealed that dentin hypersensitivity is closely accompanied with the open dentinal tubules structures. The presence of open dentinal tubules is the n1ain condition seen in the sensitive area of the exposed dentine and is in agrccrncnt V\rith the hydrodynan1ic theory proposed by BrHnnstron1. In fact. new n1aterial technology al1owed chcn1ist to synthesize nano structured Hydroxyapatite (nano llA). Nano H/\-bascd n1atcrials showed high degree of suri~1cc activity. reactive and have capability in reducing rncchanically the functional diameter of the tubules in order to minimize the dentinal permeability and therefore sensitivitY as well. The ain1 of this study is to evaluate the closure of dentinal tubules after the apJication of nanostructured and standard 11/\. Sixteen extracted hmnan n1axillary permanent prcn1olars arc used in this study. The teeth are divided into 2 groups randornly. Eight dentin discs with 3 n1n1 thickness were prepared and cut under the DE.J of the occlusal area (f(ntr discs) and cervical area (four discs). Each group has eight dentin discs. A11 the dentine smnples \Vcrc treated with an EDTA solution (pH 7.4) for 1 n1inute to remove the all sn1car layer. lla1f discs of Group I were treated for 5 minutes with carhoxymethylcellu1ose (CMC) gel containing nano structured BA and Group II with standard HI\. The other half discs were ren1aining untreated as a control. All specin1ens then washed in running V\'atcr for 5 111inu1es. All specin1ens were examined under SEJ\1 at magnifications of x1500 to x2000. The percentage of dentinal closure of each specimen will be calculated from the Phototnicrograph of representative using an image analyzer. The study showed that the percentage of dentinal closure treated with nano structured HA was higher than standard HA. AS a conclusion of this study. nano structured HA were superior compared to standard HA in the closure of dentinal tubules.